Factors influencing survivorship of Portulacaria afra cuttings in restoration of degraded lands - Sholto-Douglas, Craig (Rhodes University, Faculty of Science, Department of Environmental Science, 2019)
Heavy over-browsing, over-grazing, and over-trampling has caused the degradation of vast areas of subtropical thicket, including parts of the Greater Addo Elephant National Park (GAENP). Severe degradation has resulted in the loss of vegetation cover and the deterioration of soils and soil functioning. The South African Department of Environmental Affairs (DEA), and specifically the Natural Resource Management Programme (NRM), have invested in restoration initiatives such as the Subtropical Thicket Restoration Programme (STRP), which has aimed to demonstrate the logistical and practical feasibility of restoring these degraded thickets by planting en masse Portulacaria afra (spekboom) cuttings. However, the planted P. afra cuttings often succumb to various abiotic and biotic stresses. This project aimed to identify various factors which may influence the survival of P. afra cuttings, including i) soil properties, ii) water (rainfall, infiltration, run-off, etc.), iii) browsing by mega-herbivores, iv) topographical features such as slope and aspect, or v) plant species or communities. Biodiversity and carbon baselines were carried out at 50 plots within the Main Camp, Darlington and Kabouga sections of the GAENP, providing pre-planting vegetation and soil data. The en masse planting of P. afra occurred following the completion of the baselines. Following a minimum rest period of three months after planting, survivorship counts were carried out at all plots. Infiltration rate had a significant positive relationship with planted P. afra survivorship across all of the sites. Positive trends between increases in litter and root biomass and planted P. afra cuttings survivorship in Kabouga were also evident. Magnesium, water-holding capacity and increasing soil clay percentage were found to have a significant negative relationship with planted P. afra survivorship in Kabouga. Aluminium, magnesium, and boron all had significant positive relationships with planted P. afra cuttings survivorship in Addo Main Camp. No soil variables had any significant relationship with survivorship of planted P. afra cuttings at Darlington. The presence of elephants (Loxidonta africana) had a significant negative relationship with planted P. afra survivorship. Plant communities in more 'moderately' degraded states, characterized by the retention of canopy dominant species, woody vegetation cover, limited bareground and higher cover of litter had higher survivorship of planted P. afra cuttings than those in more severely degraded states. The grass Panicum maximum, and forb Atriplex semibaccata were associated with positive relationships with planted P. afra survivorship across all sites. Future research should aim to develop matrices which plot likely survivorship percentages with parameters of measurable variables, such as infiltration, severity of soil capping, browsing densities, chemical indicators, and degradation severity, to identify suitable biophysical planting conditions for P. afra cuttings. Further research should assess whether the presence of elephants, in high densities, can reduce the economic feasibility of the en masse plantings of P. afra cuttings in attempts to restore degraded landscapes.
Keywords: Uncatalogued